Analisis Alat Telekomunikasi, Sumber Daya Awak Kapal, Kelaiklautan Kapal dan Pemanduan Terhadap Keselamatan Pelayaran di Pelabuhan Bukit Batu - Sutini, Sutini; Muasyaroh, Riska (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
This research was carried out to determine the factors that influence telecommunications equipment, ship crew resources, ship seaworthiness and pilotage of cruisers at Bukit Batu port. Data collection was carrie d o ut th r o u gh observation, literature study, interviews, documentation and questionnaires. Th is research uses a non-probability sampling technique, namely the ce ns u s me th o d . The data analysis used in this research is descriptive and quantitative analysis. The data is analyzed using multiple linear regression analysis with the help of th e Statistical Pack age For Social (SPSS) version 25 software. Based on the research results, it can be seen that the research model of the multiple linear regression equation is Y= -0.219 + 0.308.X1 + 0.200.X2 + 0,192.X3 + 0.349. X4 + µ. Where the variables Safety (Y), Telecommunication Equipment (X1), Crew Resources (X2), Ship Seaworthiness (X3) and Guidance (X4) were tested using the t test showing that the four independent variables partially have a significan t influence on consumer decisions as the dependent variable. The Adjusted R Square figure of 0.837 shows that 83.7 percent of consumer decision variables can be explained through the four independent variables in the regression equation. Meanwhile, the remaining 16.3 percent is explained by other variables outside the four variables used in this research.